Six new and one known species of Geomonhystera (Nematoda, Monhysteridae) from moss, an epiphytic plant and soil in México and Ecuador - Prado-Vera, Ignacio Cid Del; Ferris, Howard; Subbotin, Sergei A. (Zootaxa, 2018)
Six new species of Geomonhystera (Nematoda, Monhysterida: Monhysteridae) Andrássy, 1981, are described and illustrated, five from México and one from Ecuador. The new species have many features in common and in common with at least several other species of the genus. Consequently, those features individually are not very useful for species-level diagnosis. They include the cuticular striation which, under light microscopy, ranges from fine to apparently smooth; however, scanning electron micrographs reveal very fine cuticular striation on all the new species. All the new species have a few body setae scattered along the length of the body and the vulval lips of females are slightly protruding. As for other species of the genus, there is considerable overlap in the ranges of standard morphometric characters so a combination of standard and additional morphometrics, as well as qualitative characters, is necessary for species separation. Geomonhystera mexiquense sp. n., collected from moss on a rock and on the trunk of Quercus crassipes in Juchitepec, México State, México, has outer labial setae that are unsegmented and 44–67% of the head width, the cephalic setae are thin, unsegmented and 31–50% of the head width; the vulval lips protrude slightly. Geomonhystera michoacana sp. n., collected from moss on a rock in Tzararacua National Park, Uruapan, Michoacan State, México, has a very finely-striated cuticle which appears almost smooth and bears rare cervical and caudal setae; the tail is long, 15–17% of the body length, and the rectum also is long, 23–32 (27±2.0) µm. Geomonhystera longispiculata sp. n., collected from an epiphytic plant in the botanical garden of the Ecology Institute in Jalapa, Veracruz State, México, is distinguished from all the species of the genus by the long, slender spicules, 55–85 (75±3.0) µm. The cuticle has conspicuous fine striation and there are somatic setae scattered along the body. Geomonhystera ecuatoriana sp. n., collected from moss on the trunk of Scalesia pedunculata growing on the twin volcanoes of Isla Santa Cruz, Galapagos, Ecuador, has fine cuticular striation and a few small body setae; the unsegmented outer labial setae are 42–54% of the head width and the cephalic setae are thin, unsegmented and 33–45% of the head width; the vulval lips protrude slightly and the vulva-anus distance is 37–48 µm or 2.1–2.5 times anal body diameter. Males of G. ecuatoriana have slightly arcuate spicules, 35 µm long. Geomonhystera galindoi sp. n., collected from moss on the trunk of Quercus peduncularis in San Pablo Ixzayo, Texcoco, México State, México, has fine cuticlar striation and a few fine body setae, the vulval lips are slightly protruding; the vulva-anus distance is 35–50 (41±0.9) µm, 1.5–2.2 (1.9±0.2) times anal body diameter. Males of G. galindoi are slightly ventrally curved with the posterior end strongly curved, giving the body a hook-shaped appearance. Geomonhystera chiautzingoensis sp. n., collected from moss on the trunk of Crataegus mexicana in Chiautzingo, Puebla State, México, has exceedingly fine striation of the cuticle and outer labial and cephalic setae that are less than 50% of the head width. Additionally, G. dubia Siddiqi & Shahina, 2004 was sollected in soil samples around a plum tree (Prunus sp.) in the garden of Montecillo Campus, Colegio de Postgraduados, Texcoco, México State, México This species has a small body with fine cuticular striation and a few sparsely-distributed body setae; the outer labial and cephalic setae are unsegmented, 5–8 and 3–5 µm long, 56–80% and 33–50% of the head width, respectively; the vulval lips protrude slightly but are sometimes flush with the body contour.